PENGARUH PERUBAHAN TEMPERATUR AIR PENDINGIN TERHADAP SAAT PENYALAAN PADA MOTOR BENSIN - Zaenuri, Tri Yuswidjajanto; Hariyanto, Arief; Yanto, Harki Apri (Mesin, 2003)
This paper contains the testing of a spark ignition engine to observe the influence of the engine temperature variation on the ignition timing. The engine temperature of Toyota 7K equipped with EFI self developed by LMBSP is varied and the performance test is conducted over the variations of load and rpm, which simulate the real condition on the road. The aim of the experiments is to yield the ignition timing which produces the optimum performance at any load condition.